Spatiotemporal Impact of Precipitation Trend on LULC Using Satellite Remote Sensing Technique in Khirthar National Park, Sindh Pakistan - Soomro, Abdul Ghani; Memon, Aneela Hameem; Mahar, Gohar Ali; Gadehi, Mumtaz Ali; Azam, Muhammad (International Journal of Economic and Environmental Geology, 2023)
Water footprint techniques are extensively used for essential life chores. It also maintains the natural ecosystem. The variations in climatic spell are not only important to investigate the past and current scenarios, but it is also useful to develop the water resource projects. The current study explored the spatial-temporal climatic variation of dry and wet periods (between 1998 and 2010) using the digital image processing technique of ENVI (Environment for Visualizing Images) classics, satellite remote sensing g (SRS), and GIS. The results are organized for the reported period i.e. between 1998 and 2010, showing the change detection of the hydrological effect in the dry and wet years. It shows a significant change in the land use land cover (LULC) of vegetation, water, settlement, and ephemeral rivers followed by 91%, 97.45%, 94.40%, and 62.94 % respectively through the wet year of 2010, in association with the dry period of 1998. For more authentications, the Normalized Difference Vegetative Index (NDVI) image difference of the wet and dry period has also been evaluated, which has shown vegetation in large areas with more water potential in the wet year 2010. The water potential can be used by diverting it to the natural depressions, ditches, and ponds for storage purposes and to increase recharge of groundwater by increasing its quality and quantity. The stored water could be utilized in the drought-prone days for sustainable agriculture activities, to reduce the migra